2009
DOI: 10.1016/j.cell.2009.08.031
|View full text |Cite
|
Sign up to set email alerts
|

A Genome-wide RNAi Screen for Modifiers of the Circadian Clock in Human Cells

Abstract: Summary Two decades of research identified more than a dozen clock genes and defined a biochemical feedback mechanism of circadian oscillator function. To identify additional clock genes and modifiers, we conducted a genome-wide siRNA screen in a human cellular clock model. Knockdown of nearly a thousand genes reduced rhythm amplitude. Potent effects on period length or increased amplitude were less frequent; we found hundreds of these and confirmed them in secondary screens. Characterization of a subset of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

34
418
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 404 publications
(461 citation statements)
references
References 44 publications
34
418
0
1
Order By: Relevance
“…5D). Especially, it has been reported that Dbp gene expression level directly reflects BMAL1/CLOCK-mediated transcriptional activity via Ebox enhancer elements (29). Therefore, these results suggest dysfunction of the BMAL1/CLOCK-regulated canonical circadian feedback loops in ES cells.…”
Section: Expression Of Clock Genes In Es Cells Ips Cells and Differmentioning
confidence: 71%
“…5D). Especially, it has been reported that Dbp gene expression level directly reflects BMAL1/CLOCK-mediated transcriptional activity via Ebox enhancer elements (29). Therefore, these results suggest dysfunction of the BMAL1/CLOCK-regulated canonical circadian feedback loops in ES cells.…”
Section: Expression Of Clock Genes In Es Cells Ips Cells and Differmentioning
confidence: 71%
“…S5 D-F), the "master" oscillator in mammals that coordinates circadian rhythms throughout the body (33). To establish whether these genes influence clock function in human U2 OS cells, we used data from the BioGPS portal (34,35). Interestingly, two independent RNAi knockdown experiments of LSM7 generated a long period phenotype similar to that observed when knocking down the CRY2 core clock gene (Fig.…”
Section: A Mutation In Arabidopsis Lsm5 Confers a Long Period Phenotymentioning
confidence: 99%
“…Recently, genome-wide reverse genetic screens using RNAi libraries have identified a large number of possible modifiers of the circadian clock using human cell lines (Maier et al, 2009;Zhang et al, 2009).…”
mentioning
confidence: 99%